Alcohol septal ablation for hypertrophic obstructive cardiomyopathy: a review of the literature - Veselka, Josef (Medical science monitor, 2007)
Hypertrophic obstructive cardiomyopathy (HOCM) is a common inheritable cardiac disorder that can lead to symptoms of dyspnea, angina pectoris, and syncope. Symptomatic patients are usually treated with negatively inotropic agents, such as beta-blockers, calcium channel blockers, or disopyramide. However, up to 10% of patients with outflow pressure gradient are unresponsive to medical therapy. Until the early 1990s, surgical myectomy represented the standard treatment for patients with HOCM and drug-refractory symptoms. More than one decade ago, alcohol septal ablation (ASA) was introduced as a less invasive alternative therapy for symptomatic HCM patients with obstruction. ASA is performed through a percutaneous approach, in which 1-3 ml of absolute alcohol is introduced into the septal branch to create a controlled septal infarction of the basal interventricular septum. This procedure results in relief of symptoms, a decrease in the pressure gradient, and improvement in left ventricular diastolic function. A randomized controlled trial is needed to compare ASA and surgical myectomy in order to determine which technique provides maximal benefit.
Keywords: katetrizační ablace; srdeční septum; Catheter Ablation; Ethanol; Heart Septum; ethanol; Humans; Cardiomyopathy, Hypertrophic; hypertrofická kardiomyopatie; lidé